The effect of training with educational video media based on local wisdom on mothers' level of knowledge and attitudes in recognizing the signs and dangers of ISPA in toddlers - Lamria Situmeang; Sulistiyani Sulistiyani; Yudi Prayitno (Science Midwifery, 2023)
This research is motivated by the importance of increasing the knowledge and attitudes of mothers of toddlers in recognizing the signs and dangers of ISPA. The aim of this research is to determine the effect of ISPA training using the Wisdom educational video media in the East Sentani regional language on the knowledge and attitudes of mothers of toddlers in recognizing the signs and dangers of ISPA. This research uses a Quasi experimental design with a pretest-posttest control group design approach. The research subjects were 82 mothers of toddlers at the Harapan Sentani Timur Health Center, Jayapura Regency, who were divided into 2 (two) groups of 41 people each, namely the control group and the intervention group. Data were analyzed statistically using the Mann-Whitney U test. The results of this study showed that there was a difference in the median difference in the posttest results of mothers of toddlers' knowledge between the intervention group and the control group. There is a difference in the median difference in the posttest results of mothers of toddlers' attitudes between the intervention group and the control group. The results of this research indicate that ISPA training with audio-visual educational wisdom videos in East Sentani is much better understood because it is the language of the local area where the population of East Sentani, the majority of whom use East Sentani in their daily lives with lecture, visual and discussion methods, has a significant influence on respondents' knowledge and attitudes regarding ISPA.